PENERAPAN MEDIA SEMPOA SEBAGAI ALAT BANTU OPERASI HITUNG BILANGAN BULAT DI SD NEGERI 057236 KEBUN UBI - Suroso; Yeni Listiana (LPPM Universitas Al Muslim, 2025)
This community service activity was motivated by the low ability of students at State Elementary School 057236 in the material on integer arithmetic operations (addition, subtraction, multiplication and division) which is very important material and basic material in mathematics related to other material. However, in reality, students' abilities in integer counting operations are still low. Students are confused about working on negative integer questions, multiplication and division. So, the application of abacus media helps teachers teach the material on whole number counting operations and helps students understand the material on integer number counting operations. This activity was held on 1-2 August 2024 at SD Negeri 057236 Kebun Ubi, with 2 teachers and 8 class IV students participating in the activity. The method of implementing activities was through demonstration, training and evaluation. Demonstrations and training on the use of the abacus were given to teachers, and evaluation methods were used to determine teachers' responses to the media and determine student learning outcomes after using the media. Based on the results of the questionnaire analysis, the teacher's response was very positive towards the use of abacus media and student learning outcomes were better after using abacus media. The average value of student learning outcomes before using abacus media was 40.625 and after using abacus media it was 78.125. Thus, the next community service activity should be carried out with limited participants because the abacus media is limited. However, if the activity has more participants, more abacus must be provided to make the implementation of the activity more effective.